# 2t+8=3

## Simple and best practice solution for 2t+8=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 2t+8=3 equation:

Simplifying 2t + 8 = 3 Reorder the terms: 8 + 2t = 3 Solving 8 + 2t = 3 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 2t = 3 + -8 Combine like terms: 8 + -8 = 0 0 + 2t = 3 + -8 2t = 3 + -8 Combine like terms: 3 + -8 = -5 2t = -5 Divide each side by '2'. t = -2.5 Simplifying t = -2.5

### See similar equations:

| 7(x+2)-(9x+3)=-5 | | 3x-8=7x+12 | | 21+4x=28 | | 6x^2+13x=-3 | | 2u+4=12 | | X-19=17-8x | | 200+15x=425 | | 11x+49=4x+22 | | 7(1-3x)-8x= | | 10j+5=75 | | 3x^3+x^2-21x-7=0 | | 7x+1=x-7 | | 2x^2-16x=18 | | 176-4x=32x+24 | | 3p-6=p-20 | | (3-1)2-1= | | 2(y+6)=3y-4 | | 10x-10=70 | | x^2+8x=-15 | | (x^2+3)(x^3+1)=0 | | x^2+3x-12=6 | | -3m+5(3-7m)= | | 11x+6+7x=26 | | 6x-1=x-3 | | 3.6=x-7.1 | | 5y-2=28-y | | (10-1)2-1= | | 10x+4=5(2x+7) | | 8+7x=74+x | | -2-4(v-5)= | | -7.9x+1.5=-64.5-1.3x | | 9n-11=79 | | 4a-5-2a+9=28 | | 5y+3=2y+15 | | -4-6x=11-9x | | 10x-7=23 | | 5(p-4)+3= | | 4x+5=-67-8x | | -16x+4y+(-10x)= | | 3x+13=94-6x | | 8-9x=88-23x | | 14=12+2x | | 142-5x=31x+22 | | 2X+17+3X-2=35 | | -45-3x=5-8x | | 64+3x=10+9x | | 6y+2w-5y= | | -2x+4+5(x+1)=-(4x-4) | | 12x(t+17)=384 | | 135-4x=4x+15 | | 12*(t-17)=384 | | 7x-10+3x+7=28 | | 8n-12=-12 | | 2(k+1)+3k= | | 3x+7+7X-10=28 | | -9+x=-12 | | 2n-6=12 | | (3-2)*3= | | 3x+7=7X-10 | | 11-8x=33-22x | | 5-c+3+3=2c+4 | | 96-6x=21x+21 | | -4-5(b+7)= | | -4x-2+7x=118 | | 7.5x^2=30 |